2017
DOI: 10.2147/ndt.s128807
|View full text |Cite
|
Sign up to set email alerts
|

Role of prediabetes in stroke

Abstract: Stroke is one of the leading causes of death and probably the greatest cause of adult disability worldwide. Diabetes mellitus (DM) is a state of accelerated aging of blood vessels. Patients with diabetes have increased risk of stroke. Hyperglycemia represents a risk factor for poor outcome following stroke, and probably is just a marker of poor outcome rather than a cause. Lowering of blood glucose levels has not been shown to improve prognosis. Also, prevention of stroke risk among patients with DM is not imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 52 publications
1
19
0
Order By: Relevance
“…In our study, we observed that 38.7% of intracerebral hemorrhage patients were defined as PreDM at admission, which is consistent with the occurrence rate of PreDM among ischemic stroke patients and the general population (Mijajlovic, Aleksic, Sternic, Mirkovic, & Bornstein, ; Vijayakumar et al, ). We found that the PreDM group had a higher risk of poor functional outcome than the non‐DM group among intracerebral hemorrhage patients.…”
Section: Discussionsupporting
confidence: 88%
“…In our study, we observed that 38.7% of intracerebral hemorrhage patients were defined as PreDM at admission, which is consistent with the occurrence rate of PreDM among ischemic stroke patients and the general population (Mijajlovic, Aleksic, Sternic, Mirkovic, & Bornstein, ; Vijayakumar et al, ). We found that the PreDM group had a higher risk of poor functional outcome than the non‐DM group among intracerebral hemorrhage patients.…”
Section: Discussionsupporting
confidence: 88%
“…The estimated prevalence of Chinese adults with prediabetes was 50.1%, and 493.4 million may have had prediabetes in 2010 [ 2 ]. Prediabetes is an important risk factor for diabetes [ 3 ] and many other diseases, such as cardiovascular diseases (CVD) [ 4 ], stroke [ 5 ], and nephropathy [ 6 ]. It was reported that the annual risk of progressing to diabetes in people with prediabetes was 5%–10% and up to 70% prediabetic patients would develop diabetes after years [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Stroke is one of the main causes of death and disability worldwide [ 1 ]. Due to lack of effective treatment, it is difficult to cure stroke patients completely.…”
Section: Introductionmentioning
confidence: 99%